1989
DOI: 10.1159/000205546
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylated Hemoglobin Levels in Sudanese Sickle Cell Anemia Patients

Abstract: Glycosylated hemoglobin was measured, by a colorimetric method, in 49 patients with sickle cell anemia attending Khartoum Teaching Hospital. The level obtained (4.9%, SD 1.3) was significantly lower than the control value (5.6%, SD 0.2; p < 0.0025). Expressed as percentage of the control value, the glycosylated hemoglobin level in these patients was 81 %. This falls midway between the 90% reported in a benign form of sickle cell anemia in Saudi Arabia and the 58% reported in a severe form in an American Black … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…They found a strong linear correlation between A1c levels and red blood cell survival ( r 2 = 0.88, P < 0.001) and suggested the use of A1c levels to estimate the degree of haemolysis in patients without diabetes [6]. Low A1c levels that are discrepant with high plasma glucose measures have been reported in diabetic patients with haemolysis of various aetiologies, such as autoimmune haemolytic anaemia [7], sickle cell anaemia [8], malaria [9], or haemolysis following cardiac surgery [10]. Unexpectedly low A1c levels were also found in three patients with haemolysis induced by medication (dapsone, trimethoprim–sulfamethoxazole, and IFN + RBV in one case) [11].…”
Section: Discussionmentioning
confidence: 99%
“…They found a strong linear correlation between A1c levels and red blood cell survival ( r 2 = 0.88, P < 0.001) and suggested the use of A1c levels to estimate the degree of haemolysis in patients without diabetes [6]. Low A1c levels that are discrepant with high plasma glucose measures have been reported in diabetic patients with haemolysis of various aetiologies, such as autoimmune haemolytic anaemia [7], sickle cell anaemia [8], malaria [9], or haemolysis following cardiac surgery [10]. Unexpectedly low A1c levels were also found in three patients with haemolysis induced by medication (dapsone, trimethoprim–sulfamethoxazole, and IFN + RBV in one case) [11].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, GHb percentage can be used as a time-averaged index of the blood glucose concentration to which the Hb has been exposed. However, unusually low GHb percentages are observed in subjects with hemolytic anemia (3)(4)(5)(6)(7). Thus, GHb concentration also is a function of the duration of exposure of Hb to blood glucose, i.e., the life span of the erythrocyte.…”
mentioning
confidence: 99%
“…For instance, a study done in Sudan by Atabani et al (10) revealed lower levels of HbA1c in children with SCA compared to children without SCA. Another study involving adults African-Americans by Lacy et al (6) also revealed lower levels of HbA1c in patients with SCT compared to those without SCT.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the wide availability of immunoassay methods in our settings, using standard cut-offs of HbA1c levels to diagnose DM in children with SCA can cause missed opportunity for interventions. Some of the patients could be missed because of the possibly false low values (10).…”
Section: De Nition Of Key Terms Introductionmentioning
confidence: 99%